Health outcomes before, during and after the great recession in Canada: A longitudinal analysis - Ehsan Latif (Review of Economic Analysis (REA), 2020)
Using panel data from Canadian National Population Health Survey (2006-2011), this study examined what happened to individuals' self-reported health during and in the aftermath of great recession of 2008-2009. The study used different methods such as ordered probit method, ordinary least square method and panel fixed effects method. Once individual specific fixed effects are controlled for, the results show that great recession had no statistically significant detrimental impact on self-reported health status. The results further show that health status in the aftermath of great recession did not significantly differ from the health status before the great recession.
Keywords: E32; I1; C23; 330; Recession; Health Outcomes; Panel Data; Canada